Wetland vegetation cover changes and its response to climate changes across Heilongjiang-Amur River Basin - Chang, Xinyue; Yu, Lingxue; Li, Guangshuai; Li, Xuan; Bao, Lun (Frontiers in Plant Science, 2023)
The Heilongjiang Amur River Basin is one of the largest and most complex aquatic systems in Asia, comprising diverse bilateral or trilateral wetland cooperation. The wetland vegetation in mid-high latitude areas has high natural value and distinctive ecosystem characteristics. In this study, we investigated the changes in leaf area index (LAI) in the Heilongjiang Amur River Basin from 2000 to 2018 based on the growing season (May to September) climate change and LAI data. Our results indicate an increase in LAI of 0.014 m2·m-2/yr in the context of a yearly climate that was both warmer and wetter. Solar radiation and minimum temperature showed a significant positive correlation with LAI in wetland vegetation. On a regional scale, wetlands in China and Russia were positively influenced by solar radiation and minimum temperature, with precipitation showing a slight lag effect. In contrast, wetland vegetation in Mongolia was positively influenced by precipitation. These correlation effects are related to the local climate region. In colder areas, the greening of the wetland vegetation in the Heilongjiang Amur River Basin was limited when precipitation was above a certain threshold value. In warmer areas, the wetland vegetation would take advantage of the hydrothermal condition and promote greening as temperature increases. Our investigation can provide a scientific foundation for the trilateral region in wetland ecosystem protection and is beneficial for a more comprehensive understanding of the responses of wetlands in the middle and high latitudes to climate change.